2021
DOI: 10.1016/j.ejphar.2021.174548
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related susceptibility in coronavirus disease 2019 (COVID-19): Proposed mechanisms

Abstract: The importance of sex differences is increasingly acknowledged in the incidence and treatment of disease. Accumulating clinical evidence demonstrates that sex differences are noticeable in COVID-19, and the prevalence, severity, and mortality rate of COVID-19 are higher among males than females. Sex-related genetic and hormonal factors and immunological responses may underlie the sex bias in COVID-19 patients. Angiotensin-converting enzyme 2 ( ACE2 ) and transmembrane protease/serine sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 137 publications
0
18
0
1
Order By: Relevance
“…Other authors did not observe a gender effect [ 12 , 23 , 38 , 39 ]; there is scarceness of literature data on this issue, and this finding should be re-evaluated with more relevant evidence from other studies. For SARS-CoV-2 infection and severity, a role has been proposed for encoding on the X-chromosome of the angiotensin-converting enzyme 2 and the largest immune-related genes leading females to develop more robust immune responses, as well as a role for sex hormones [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors did not observe a gender effect [ 12 , 23 , 38 , 39 ]; there is scarceness of literature data on this issue, and this finding should be re-evaluated with more relevant evidence from other studies. For SARS-CoV-2 infection and severity, a role has been proposed for encoding on the X-chromosome of the angiotensin-converting enzyme 2 and the largest immune-related genes leading females to develop more robust immune responses, as well as a role for sex hormones [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that the majority of excess deaths were attributable to COVID-19. Moreover, other studies have suggested that the risk of COVID-related death in males may be related to susceptibility to severe SARS-CoV-2 infections and male hormones [ 46 , 47 , 48 ]. Therefore, gender could be a risk factor for COVID-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…According to Aksoyalp and Nemutlu-Samur (2021), estrogen regulates ACE negatively and, at the same time, regulates ACE2, AT2 Receptor, and MAS enzyme positively. Therefore, higher ACE2 and Ang 1-7 production are observed in the female population than in men [ 72 ]. Estradiol also inhibits the TMPRSS2, which is needed for the virus to bind with ACE2 and increases disintegrin and metalloprotease 17 expression, which is involved in the ACE2 ectodomain cleavage, allowing higher levels of the soluble ACE2 that neutralize SARS-CoV-2 and prevent it from bonding with ACE2 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%